Entre memoria y política: las historietas de Felipe Hernández Cava sobre la España del siglo xx (1973-1996) - Eduardo Hernández Cano (Cahiers de Civilisation Espagnole Contemporaine)
The comic works of Felipe Hernández Cava developed during the first decades of the new Spanish democracy constitutes one of the most coherent intellectual interventions on the role of memory in society and its political function. Over three decades, Hernández Cava created a work in which memory acquired successive meanings and articulated different political goals in response to the changing situation in the country. From popular mobilizations against the dictatorship to denouncing the institutional oversights of democracy, Hernández Cava has tried to include adult comics in the public debate about the past and present of Spain.